Determinants of Entrepreneurial Intention among Higher Education Students: The Role of Entrepreneurship Education, Social Environment, and Self-Efficacy - Margaretha S. Kabanga; Janri D. Manafe; Tuti Setyorini (Journal of Management and Business Innovation, 2026)
This study aims to examine the determinants of entrepreneurial intention among higher education students by integrating entrepreneurship education, social environment, and self-efficacy within the Theory of Planned Behavior framework. A quantitative explanatory approach was employed using survey data collected from 231 final-year students at Kupang State Polytechnic. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess both measurement and structural models. This study extends the application of the Theory of Planned Behavior by empirically demonstrating the dominance of perceived behavioral control, represented by self-efficacy, over attitude and subjective norms in shaping entrepreneurial intention. It provides contextual evidence from an underexplored higher education setting, offering a more nuanced understanding of TPB components. The findings suggest that higher education institutions should prioritize experiential entrepreneurship learning to strengthen students’ self-efficacy, alongside fostering supportive social environments to enhance entrepreneurial intention. This study is limited by its cross-sectional design, single-institution sample, and reliance on self-reported data. Future research should adopt longitudinal approaches and incorporate broader contextual variables to improve generalizability.